Is Osteopontin a Good Marker for Bone Metastasis in Canine Mammary Gland Tumor and Prostate Cancer? - Caroline Grisoni Sanchez; Marxa Leão Figueiredo; Laíza de Sartori Camargo; Luiz Guilherme Dercore Benevenuto; Zara Alves Lacerda; Carlos Eduardo Fonseca-Alves (Animals, 2023)
Osteopontin (OPN) is a protein synthesized by a large number of cells, and its overexpression has been associated with the development and prognosis of cancer. OPN overexpression has been claimed to be a marker for the development of bone metastasis in human cancers, but no prior research has investigated the association between OPN expression and the metastasis of canine mammary gland tumors (MGTs) and prostate cancer (PC). Therefore, we investigated OPN expression in MGTs and PC samples from 50 canine patients with or without metastasis (bone vs. other sites). Higher OPN expression was detected in primary tumor samples from animals with bone metastasis than in those without bone involvement (p = 0.0321). In MGT samples, a significantly lower survival rate was observed in patients with higher OPN expression (p = 0.0171). In animals with PC, there was a strong trend toward lower survival in animals with positive OPN expression; however, this trend was not statistically significant (p = 0.0779). From these findings, it can be concluded that OPN may be a promising target for future MGTs and PC studies because of its role in enhancing cell invasion and metastasis.